Narrative of the North Polar expedition : U.S. Ship Polaris, Captain Charles Francis Hall commanding - United States. Navy Department.; Nichols, H. H. (Henry Hobart), 1816-1887, engraver.; Morgan, Henry J. (Henry James), 1842-1913, illustrator.; Smillie, T. W. (Thomas William), 1843-1917, illustrator.; Schumann, Emil, illustrator.; Bessels, Emil, 1847-1888, illustrator.; Bryan, Richard W. D., contributor.; Chester, Hubbard C., d. 1889?, contributor.; Tyson, George E. (George Emory), 1829-1906, contributor.; Davis, Charles Henry, 1807-1877, editor.; Hall, Charles Francis, 1821-1871.
This narrative has been prepared from official papers and from journals of the officers and men of the Expedition, as well as from valuable private contributions acknowledged in the text. The thread of the story of the Polaris has been drawn chiefly from a compilation made by Mr. R. W. D. Bryan, the Astronomer of the Expedition; the incidents of the ice-floe party have been furnished by the journals and note-books of Geo. E. Tyson, Assistant Navigator, and of others with him on the floe, and by the testimony given before the board organized by the Secretary of the Navy, June 5, 1873. Includes index. Wood engravings painted in oil by Mr. H.J. Morgan, from original sketches by Mr. Emil Schumann and Dr. Emil Bessels; photographed on wood by Mr. T.W. Smillie, and engraved by Mr. H.H. Nichols. Appendix: Instructions of the National academy of sciences. -- Correspondence between the British Admiralty and the United States Navy department in relation to the stores left by the Polaris expedition on the west coast of Greenland. -- Journals of Mr. H.C. Chester and Captain Geo. E. Tyson while on boat-journeys, June-July, 1872. -- Journals used in the preparation of the Narrative of the Polaris expedition. This narrative has been prepared from official papers and from journals of the officers and men of the Expedition, as well as from valuable private contributions acknowledged in the text. The thread of the story of the Polaris has been drawn chiefly from a compilation made by Mr. R. W. D. Bryan, the Astronomer of the Expedition; the incidents of the ice-floe party have been furnished by the journals and note-books of Geo. E. Tyson, Assistant Navigator, and of others with him on the floe, and by the testimony given before the board organized by the Secretary of the Navy, June 5, 1873. Mode of access: Internet. From the library of Henry J. Vaux. Red cloth with gilt-stamped illustration.